Design wind loads for transmission towers with cantilever cross-arms based on the inertial load method. Issue 205 (October 2020) - Zhao, Shuang; Yan, Zhitao; Savory, Eric
Abstract: Appropriate design wind loads can effectively avoid damage to transmission towers under strong wind and the wind-induced vibration coefficient β ( z ) is a critical parameter for determining those loads. Based on the inertial load approach, a step-by-step calculation method for the design wind loads of transmission towers considering the effects of cross-arms and diaphragms was proposed. In order to be consistent with actual transmission towers, the correction coefficient expressions of β ( z ), such as θ b, θ l and θ η, considering the influence of local shape, mass and windshield area and the spatial correlation of the fluctuating wind, respectively, were derived and investigated. By the introduction of these three coefficients, the design wind loads for transmission towers with cross-arms and diaphragms can be determined. For transmission towers with cantilever cross-arms, design wind load formulae were derived, based on the analyses of 6 tower samples. The example of an actual transmission tower was used to verify the correctness of the derived formulae. The parameter analyses of the design wind loads showed that cross-arms have a great influence on β ( z ) and the wind-induced vibration response of transmission towers, but diaphragms only have a marginal influence and so may be neglected in the approximate calculation of the design wind loads. The research results provide a calculation method for the wind-resistant design of transmission towers. Highlights: The influence of cross-arms on wind-induced vibration of towers is not negligible. Diaphragms have a small influence on the wind-induced vibration of towers. The influence of cross-arms and diaphragms on design wind loads can be tabulated. Design wind loads for transmission towers with cantilever cross-arms are derived. The present design wind load methodology may help improve tower design codes.